THE EFFECT OF SELF-EFFICACY AND SOCIAL SUPPORT ON SELF-ADJUSTMENT IN STUDENTS AT PANJATEK VOCATIONAL HIGH SCHOOL IN BEKASI - Maya Pramaisella; Puji Wahono; Maulana Amirul Adha (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
This study aims to determine the effect of Self-Efficacy (X1) and Social Support (X2) on Self-Adjustment (Y) among students at SMK Panjatek Bekasi. This study uses a quantitative approach with a survey method as the data collection technique. The population consists of 366 tenth-grade students at SMK Panjatek Bekasi, with a sample size of 177 students determined based on the Isaac & Michael table. The sampling technique used is probability sampling of the proportionate random sampling type. The research instrument was a Likert-scale questionnaire. Data were analyzed using SPSS version 27.0. The analysis techniques included classical assumption tests (normality, linearity, multicollinearity, and heteroscedasticity), multiple linear regression, hypothesis testing (t-test and F-test), and determination coefficient testing (R²). The test results showed that the data were normally distributed, the relationship between variables was linear, there was no multicollinearity (VIF < 10, Tolerance > 0.1), and the data were free from heteroscedasticity. The results of the multiple linear regression indicate that Self-Efficacy and Social Support simultaneously and partially influence Self-Adjustment (Sig. < 0.05). The conclusion of this study is that self-efficacy and social support have a positive and significant effect on self-adjustment among 10th-grade students at SMK Panjatek Bekasi.